CRM as a Tool for Knowledge Management in the Banking Sector - Ivanović, Teodora (International Scientific Conference Strategic Management and Decision Support Systems in Strategic Management, 2021)
We are witnessing a new market era characterized by great dynamism, competitiveness, and digitalization. Banks increasingly have to fight for their market share as well as for the loyalty of their customers. Business strategies that do not change in line with new innovations and directions can be market endangered. In order to reduce this risk, most banks choose to focus on their clients and to create knowledge about them based on data collected, both internally and externally. For the same reason, the introduction of CRM (Customer Relationship Management) is a necessary strategy of every bank. Today, there is a large amount of data (Big Data) that needs to be collected, stored, analyzed, and systematized into applicable customer knowledge. The way in which this data is collected, how it is managed, and what benefits banks have from it will be explained in this paper. Based on a review of professional literature, the author will try to answer the question of what are the goals of CRM implementation in bank operations, what are all stages of CRM development, what are the functionalities of CRM, and what are the recognized benefits of this new business strategy in the banking sector.